Pengaruh Penerapan Pendekatan Kontekstual Terhadap Kemampuan Berpikir Kritis Matematika Siswa SMP St.Thomas 1 Medan - Br. Barus, Elsa Manora (Unika Santo Thomas Medan, 2018)
The study aimed to determine the effect of applying a contextual approach to students' critical thinking skills in mathematics on cube and beam material. This research is a quasi-experimental quantitative research design with pretest-posttest control group design. The population in this study were eighth-grade students at Junior High School ofÂ St. Thomas 1 Medan. The sample in the study was selected by random sampling consisting of the experimental class (VIII-D) and the control class (VIII-E). The pretest and posttest results were analyzed using the normality and homogeneity test and the results showed that the samples were normally distributed and homogeneous. Furthermore, a correlation and regression test was conducted to describe the relationship between contextual approaches and students' critical thinking skills. Based on correlation and regression analysis, the results obtained that the application of the contextual approach has a positive effect with the correlation coefficients of the experimental class and the control class respectively 0.914 and 0.860 and the coefficient of determination is 83.5% and 73.9% respectively. So that the application of a contextual approach has a better effect on students' critical thinking skills compared to conventional learning. Based on the results of the calculation of the test of the difference in the two average mathematical critical thinking skills obtained by tcount = 2.113 > ttable = 1.99, then the hypothesis Ho is rejected. So it is concluded that the average increase in critical thinking skills of students who get learning with contextual approaches is higher than students who get conventional learning.